2016
DOI: 10.11144/javeriana.upsy15-2.qacc
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative analysis on cycle commuting in two cities with different cycling environments and policies

Abstract: a b s t r a c tThis work presents the results of a qualitative study of the rating of the bicycle as the transport mode to travel to the workplace. Twenty-one semistructured interviews were performed in two Spanish cities, Vitoria-Gasteiz and Madrid, with different cycling infrastructures and percentages of bicycle usage. The results were categorized and interpreted within the framework of the theory of planned behavior (Ajzen, 1991). The results indicate that the bicycle is considered a reliable and flexible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 43 publications
1
11
0
1
Order By: Relevance
“…In line with other findings on the basis of qualitative and quantitative analysis in Spain (Lois et al, 2016;Lois et al, 2015), Muñoz et al (2013) have identified two underlying factors among attitudinal variables, namely: direct benefits of cycling (such as reliability, comfort, safety, weather independence and relative speed) and long-term benefits (such as health benefits, quality of life, flexibility and environmental benefits). Three barriers have also been found, i.e.…”
Section: Previous Research On Bicycle Use In Madridsupporting
confidence: 79%
See 2 more Smart Citations
“…In line with other findings on the basis of qualitative and quantitative analysis in Spain (Lois et al, 2016;Lois et al, 2015), Muñoz et al (2013) have identified two underlying factors among attitudinal variables, namely: direct benefits of cycling (such as reliability, comfort, safety, weather independence and relative speed) and long-term benefits (such as health benefits, quality of life, flexibility and environmental benefits). Three barriers have also been found, i.e.…”
Section: Previous Research On Bicycle Use In Madridsupporting
confidence: 79%
“…An extensive research has explored the role of experience in utilitarian cycling (Rondinella, 2015;Rondinella et al, 2012). A comparison has also been done to highlight different commuting patterns in Madrid and another city with a different cycling environment and policy through semi-structured interviews (Lois et al, 2016).…”
Section: Theories and Statistical Methods For Data Collection And Anamentioning
confidence: 99%
See 1 more Smart Citation
“…This investigation was preceded by a qualitative study (Lois et al, 2015) consisting of the thematic analysis (Braun & Clarke, 2006) of 21 semi-structured interviews. In that study we examined the beliefs of cyclists and non-cyclists about commuting trips by bicycle in Vitoria-Gasteiz, the city where data for this research were collected.…”
Section: Research Objectivesmentioning
confidence: 99%
“…Evidence suggests that cycling has surged in popularity as a resilient and reliable travel option during the pandemic (Bryant 2020; UN News 2020), and as a consequence many cities have slowly been establishing policies, plans, and infrastructure to support biking. Most cities were already full of potential cyclists, people who were interested in taking up cycling but concerned about safety risks Lois et al 2016;Dill and McNeil 2016;Félix et al 2017). Now, people around the world have taken to bikes in order to reduce their risk of exposure to the virus when they need to travel.…”
Section: Introductionmentioning
confidence: 99%